Synthesis and characterization of cobalt supported TiO2 with Mn/Zn/Zr promoters for fischer tropsch synthesis - Mohamad Firdaus, Mohamad Ghazali (2012)
This research about the synthesis and characterization cobalt supported TiO2 catalyst for Fischer–Tropsch synthesis (FTS) producing clean and best fuel.In variety of type of promoters, the effect is determined.The catalytic material will be prepared by impregnation of a mesoporous molecular sieve based on silica which is TiO2 as cobalt catalytic supporters and Zn/Zr/Mn as promoters for comparison purposes.All materials will be used characterizing by several physico-chemical techniques such as SEM,TGA, FTIR.The catalytic and characterization results achieve give a great influence of mesoporous support porosity on the structure, reducibility and Fischer-Tropsch synthesis catalytic behavior of cobalt oxide species supported over these ordered materials.The size of supported cobalt oxide species formed during the calcination step increased with the average pore size (Dp) of the mesoporous support. Thus, the catalyst with larger Co oxide species located in wide pore silica showed to be easily reducible, more active and very selective toward the fuel fraction.The additional of promoters will be used to increase the performances of Fischer-Tropsch synthesis.